Metode ARTS Sebagai Upaya Meningkatkan Keterampilan Solfegio Mahasiswa Prodi Pendidikan Musik di Jurusan Sendratasik FBS Universitas Negeri Padang - Jagar Lumbantoruan (Program Studi Pendidikan Musik FBS UNP, 2021)
This study aims to describe the ARTS method as an effort to improve the solfegio skills of music study students in the Department of Drama, FBS, Padang State University. This research is a quasi-experimental research using descriptive analytic approach. The results of the study found that applying the four stages in the ARTS method could improve Solfegio skills, namely: (1) the preparation stage, namely designing the subject matter. (2) Presentation stage, namely the explanation of the concept of rhythm, interval, melody, and transfiguration of note units. (3) Practice stages or exercises, namely Audio, Reproduction, Transcription, and Sight-reading/ Sight-singing exercises. (4) Stages of performance, namely assessment. This research is expected to be a guide in learning solfegio, both at the elementary and tertiary levels